The Nuclear 35S rDNA World in Plant Systematics and Evolution: A Primer of Cautions and Common Misconceptions in Cytogenetic Studies - Rosselló, Josep A.; Maravilla, Alexis J.; Rosato, Marcela (Frontiers in Plant Science, 2022)
The ubiquitous presence of rDNA genes in nuclear, plastid and mitochondrialgenomes have provided an opportunity to use genomic markers to infer patterns ofmolecular and organismic evolution and assess systematic issues across the treeof life. The number, size, location and activity of the 35S rDNA cistrons in plantkaryotypes have been used as conventional cytogenetic landmarks. Their scrutiny hasbeen of utility to infer patterns of chromosomal evolution and the data havebeen used as a proxy for assessing species discrimination, populationdifferentiation and evolutionary relationships. The correct interpretation of rDNA markers inplant taxonomy and evolution is not free of drawbacks given the complexitiesderived from the lability of the genetic architecture, the diverse patterns ofmolecular change, and the fate and evolutionary dynamics of the rDNA units inhybrids and polyploid species. In addition, the terminology used by independentauthors is somewhat vague, which often complicates comparisons. To date, no effortsaddressing the potential problems and limitations involved in generating,utilizing, and interpreting the 35S rDNA data in cytogenetics have been reported. This review discusses the main technical and conceptual limitations of these rDNAmarkers obtained by cytological and karyological experimental work to clarifybiological and evolutionary inferences postulated in a systematic and phylogeneticcontext. Also, we provide clarification for some ambiguity and misconceptions interminology usually found in published work that may help to improve the usage ofthe 35S ribosomal world in plant evolution.